Emerging Patterns in Open Access Publishing: A Scopus-Based Analysis of Publishers, Countries, and Costs - B.M, Prasanna Kumar; Y, Sachin (Journal of Data Science, Informetrics, and Citation Studies)
Open Access (OA) publishing has changed academic communication, making knowledge freely and quickly available to everyone. Major publishers are publishing more journals adopting hybrid and full OA models. The study will examine OA and hybrid journals of major publishers based on Scopus data, country-wise comparison of OA publications, subject-wise average publication fee analysis and emerging OA patterns. In the descriptive-analytic method, the data collected from the Scopus database is catalogued and analysed. Elsevier ranks first with 2588 total publications, followed by Springer Nature (2473) and Taylor & Francis (2364). Spain (43.84%) is the leader in OA percentage. The average publication fee in the Medicine category is $2,800, with no APC charged on the Diamond models. Open Access publishing is shaping a democratic, not-for-profit, data-driven movement for future search communication.
Keywords: Open Access Publishing; Gold Open Access; Diamond Open Access; Publishing Models; Open Access Journals; APCs.